Tradução e Práticas Político-culturais - Rodrigues, Cristina Carneiro (TradTerm, 1994)
The opposition between domesticating and foreignizing translation is analyzed from two divergent conceptions. The first one, adopted by Campos (3), Reiβ (12) and Vermeer (15), is that the choice between one or other direction is ideologically neutral. The second one, supported by Venuti (13, 14) and Meschonnic (7), asserts that the choice is ideologically engaged. The relations established by Reiβ between these two translation methods and the concepts of dynamic equivalence and formal correspondence, presented by Nida (11), are employed to discuss such opposition and to show that translation is a socio-political practice which may be related to cultural imperialism - an issue which has been concealed by traditional translation theories.